Transfer of computer-aided diagnosis of dyspepsia from one geographical area to another. Issue 8 (August 1976) - Horrocks, J C; Lambert, D E; McAdam, W A; Morgan, A G; Pacsoo, C; Darnborough, A; De Dombal, F T
Abstract : This paper reports a comparison in Airedale District General Hospital between computer-aided diagnosis of dyspepsia and endoscopy in a prospective unselected series of 165 patients. Patients were interviewed immediately before endoscopy and the findings analysed by a small desk-top computer-aided system. Each 'new' patient was compared by the computer with a group of 360 similar patients from Leeds (25 miles away). Overall, 83% of the positive lesions found at endoscopy were correctly predicted by the computer, including all but three of the 22 cases of gastric cancer. It is suggested (1) that there is little loss of accuracy in transferring the computer-aided system from one locality to another; and (2) that a computer-aided analysis of the patient interview may be of value in selecting 'high-risk' patients for intensive investigation.